Assessment of Nebulizer Therapy Knowledge among Mothers of Children with Asthma - Kareem , Samar Hussein; Aziz, Afifa Radha (Iraqi National Journal of Nursing Specialties, 2024)
Objective(s): To assess of mothers’ knowledge of using nebulizer therapy for their children with asthma, and to find out the relationship between the mother knowledge and their socio-demographic characteristics. Methods: Descriptive study design was conducted at Ibn- Albaladi Hospital for Maternity and Child. Data were collected from October 10th, 2022 to January 10th, 2023. Purposive non-probability sample consisting of 50 mothers of children with asthma was admitted to the hospital. Data were collected through the interview technique using questionnaire consisting of: 11 items regarding mothers sociodemographic characteristics; and 19 items related to the use of nebulizer therapy for their asthmatic children. Data was analyzed by using descriptive and inferential statistical. Result: The results showed that most mothers had moderate level knowledge toward using of nebulizer therapy for their children with asthma with (58%) of them, with arithmetic mean of (M±SD= 2.19±0.305). There was no significant correlation between mothers’ age, marital status, family income, and their level of knowledge at (P < 0.05). Conclusion: The study concludes that mothers’ level of knowledge regarding the using of nebulizer therapy was at moderate level. Recommendations: This study emphases applying and distributing of instructional pamphlets among mother of children with asthma regarding using nebulizer therapy and enhancing their knowledge through social media to improve their practice.